KINERJA PROGRAM PEMBERDAYAAN MASYARAKAT DESA DI KECAMATAN BOLANGITAN BARAT KABUPATEN BOLAANG MONGONDOW UTARA - KINONTOA, RIZKY FAIZ; POSUMAH, JOHNNY; PLANGITEN, NOVVA (Sam Ratulangi University, 2022)
The purpose of this study is to determine how the performance of the communityempowerment program in the District of West Bolangitan, North Bolaang Mongondow Regency.The research used a qualitative approach method. The performance of the communityempowerment program is seen from the five indicators or dimensions of the performance of theempowerment program from UNICEF, namely: welfare, access, critical awareness, participation, andcontrol. The research informants were three village heads and six community members in the threeresearch villages. Data collection using interview guidelines, while the analysis technique used isinteractive model analysis.Based on the results of the study, conclusions were drawn: (1) The dimension of